PMPA for nephroprotection in PSMA-targeted radionuclide therapy of prostate cancer - Kratochwil, Clemens; Giesel, Frederik L.; Leotta, Karin; Hoppe-Tichy, Torsten; Haberkorn, Uwe (Journal of nuclear medicine, 2015)
Radioactive ligands for the prostate-specific membrane antigen (PSMA) are under development for therapy of metastasized prostate cancer. Since PSMA expression is also found in the kidneys, renal tracer uptake can be dose-limiting. Because kidney kinetics differ from tumor kinetics, serial application of PSMA inhibitors such as 2-(phosphonomethyl)pentanedioic acid (PMPA) may improve the kidney-to-tumor ratio. In this study, we evaluated the effect of PMPA on the biodistribution of 2 promising PSMA ligands. Methods: Human prostate cancer xenografts (LNCaP) were transplanted subcutaneously into mice. After injection of 125I-MIP1095, a 16-h latency period was allowed for tracer clearance from the blood and renal calices. After baseline scintigraphy, PMPA was injected in doses of 0.2-50 mg/kg (n = 3 per dose, 5 controls), followed by scans at 2, 4, 6, and 24 h after PMPA injection. Kidney and tumor displacement was determined as a percentage of baseline. A shortened but similar design was used to evaluate the PSMA ligand MIP1404, which contains a chelate for 99mTc/rhenium. Results: PMPA injection 16 h after MIP1095 translated into a rapid and quantitative relevant displacement of renal activity. Tumor uptake was reduced to a significantly lesser extent in a dose-dependent manner. PMPA doses of 0.2-1 mg/kg appear optimal for sustaining nearly complete tumor uptake while simultaneously achieving near-total blocking of specific renal PSMA binding. The effect was successfully validated with the PSMA ligand MIP1404. Conclusion: PSMA-targeted radionuclide therapy can benefit from serial PMPA comedication by reducing off-target radiation to the kidneys. These data will be used for a first approximation in clinical translation, although in patients an optimization of the dose and time schedule may be necessary.